Experimental study of asphaltene deposition in transparent microchannels using the light absorption method. Issue 5 (4th May 2018) - Zhuang, Y.; Goharzadeh, A.; Lin, Y. J.; Yap, Y. F.; Chai, J. C.; Mathew, N.; Vargas, F.; Biswal, Sibani L.
ABSTRACT: This study focuses on an experimental investigation of asphaltene deposition in a vertical transparent microchannel. Heptane-induced asphaltene precipitation is utilized to precipitate dissolved asphaltene in crude oil into asphaltene particles at ambient temperature and standard atmospheric pressure. These asphaltene particles deposit gradually on the surface of microchannels. The key parameters that influence the mechanism of asphaltene deposition are the ratio of crude oil to n-heptane and experimental elapsed time. At a constant flowrate, the amount of asphaltene deposited on a transparent channel wall is quantified using a new flow visualization technique based on reflected light intensity and image analysis. Asphaltene precipitation and deposition strongly affect the reflected light intensity through the change of mixture color in the recorded images. Experimental results show that asphaltene deposition process follows three stages, (i) slow asphaltene particle deposition at the beginning of the experiment, (ii) a rapid and continuous deposition occurring after few hours and (iii) a slower deposition (decreasing deposition rate) at the end of the experimentation. The experimental results for different crude oil to n-heptane ratios illustrate that deposition increases with this ratio, i.e. increasing concentration of n-heptane. An empirical equation is developed to correlate the intensity of the light absorption to the thickness of the deposited asphaltene in a transparent microchannel. Non-uniform deposition along the longitudinal direction of the microchannel is characterized. Deposits decrease with increasing longitudinal distance from the inlet. This non-uniform deposition distribution is due to local mass transport limitations and asphaltene aggregation size effect. GRAPHICAL ABSTRACT: